Effects of Vanadate on Prostacyclin and Endothelin-1 Production and Protein-Tyrosine Phosphorylation in Human Endothelial Cells - Shimizu, Hiromasa; Takayama, Hiroshi; Lee, Jong-Dae; Satake, Kazuo; Taniguchi, Takanobu; Yamamura, Hirohei; Nakamura, Toru (Thrombosis and Haemostasis, 1994)
The ability of vanadate, an inhibitor of protein-tyrosine phosphatases, to affect the production of prostacyclin (PGI2) and endothelin-1 (ET-1) and protein-tyrosine phosphorylation in human umbilical vein endothelial cells (HUVEC) was studied. The addition of vanadate to monolayers of cultured HUVEC caused a sustained release of PGI2 from HUVEC in a time- and dose-dependent manner. When aspirin-treated HUVEC, which have lost the ability to increase PGI2 production in response to arachidonate, were incubated with vanadate, the cells recovered their ability to increase PGI2 production in response to arachidonate. This recovery of inducible PGI2 production in aspirin-treated HUVEC was completely inhibited either by cycloheximide, a protein synthesis inhibitor, or by actinomycin D, an RNA synthesis inhibitor. In contrast, the same concentration of vanadate suppressed the basal release of ET-1 from HUVEC. Vanadate also caused an increase in protein-tyrosine phosphorylation in HUVEC. These data indicate that vanadate induces opposite effects on PGI2 and ET-1 production with a concomitant increase in protein-tyrosine phosphorylation in HUVEC.